THE CORRELATION BETWEEN STUDENT ANXIETY AND STUDENT SPEAKING SKILL AT ENGLISH DEPARTMENT STUDENTS OF MUHAMMADIYAH UNIVERSITY OF PONOROGO - Heri Susanto; Risqi Ekanti Ayuningtyas Palupi; Dyah Atiek Mustikawati (Universitas Muhammadiyah Ponorogo, 2017)
Anxiety is one of the individual characteristics of the people. Anxiety is described as an uncontrollable state that can make the language learning situation problematic and stressful. Then, English speaking skill is very important for people interaction where people almost speak everywhere and every day through English. Speaking is one way to communicate ideas and thought a feeling and expression orally. The researcher is curious about its connection. That is why the researcher would like to find the corellation between student’s anxiety and student’s speaking skill especially for students of English education Department of Muhammadiyah University of Ponorogo. The subject of this research is the students of English Education Departmen of Muhammadiyah University of Ponorogo from semester II until VI with number of 52 Students. The researcher took all of the students as the sample of this research because the population is less than 100 people. The research was started on 5th June, 2017 until 19th June, 2017. The research used two instruments in collecting data, they were; speaking anxiety questionnaire and student achievement. Besides that, the researcher used the quantitative technique to analyze the data. Based on the result of this research, the score showed that there is significant correlation between variable X as the student anxiety and variable Y as the student speaking skill. It means that if the anxiety level of the student is high, the speaking of the students also low. Where the student feel worry, nervous, self-doubt, and unconfident when the student try to speaking with English in front of their friends, partner or in front of class. While, if the anxiety level of the studenr is low, the speaking of the student is high or good. Where the student when try to speak with English, they show the optimistic aptitude, good confident and feel enjoyful. Finally, the researcher gives suggestion that the students who want to increase their speaking skill, need to hold down their anxiety feelings with always practice and practice their speaking. Last, the researcher hopes that the result of this study will be useful for the next researcher.